In Situ Quantification of the Local Electrocatalytic Activity via Electrochemical Scanning Tunneling Microscopy. Issue 2 (29th September 2020) - Haid, Richard W.; Kluge, Regina M.; Liang, Yunchang; Bandarenka, Aliaksandr S.
Abstract: Identification of catalytically active sites at solid/liquid interfaces under reaction conditions is an essential task to improve the catalyst design for sustainable energy devices. Electrochemical scanning tunneling microscopy (EC‐STM) combines the control of the surface reactions with imaging on a nanoscale. When performing EC‐STM under reaction conditions, the recorded analytical signal shows higher fluctuations (noise) at active sites compared to non‐active sites (noise‐EC‐STM or n‐EC‐STM). In the past, this approach has been proven as a valid tool to identify the location of active sites. In this work, the authors show that this method can be extended to obtain quantitative information of the local activity. For the platinum(111) surface under oxygen reduction reaction conditions, a linear relationship between the STM noise level and a measure of reactivity, the turn‐over frequency is found. Since it is known that the most active sites for this system are located at concave sites, the method has been applied to quantify the activity at steps. The obtained activity enhancement factors appeared to be in good agreement with the literature. Thus, n‐EC‐STM is a powerful method not only to in situ identify the location of active sites but also to determine and compare local reactivity. Abstract : Optimization of catalytic materials is one of the key objectives of electrocatalytic research. In this light, the active sites of catalytic materials need to be not only found but also quantitatively characterized. Using the proposed method allows to gain highly localized, quantitative information of surface sites, acquired in situ with an electrochemical scanning tunneling microscopy setup.